THE IMPACT OF THE USE OF CREDIT SERVICES ON THE FINANCIAL SECURITY OF HOUSEHOLDS IN UKRAINE - Yehorycheva, S.; Vertebnyi, I. (Socio-economic relations in the digital society, 2021)
The aim of the article is to assess the impact of the use of credit services on the current state of financial security of households in Ukraine. It is proposed to understand the financial security of a household as the protection of its financial interests, which are determined by the needs of its members in a dignified life and comprehensive development, from external threats and internal destabilizing factors. It has been identified the trend to increase the volume of lending to individuals by financial institutions and especially — financial companies, which hadn’t been changed by the pandemic situation. At the same time the average debt burden of households remains insignificant. The authors argue that there is a special financial insecurity of clients of financial companies due to the confusing lending conditions and extremely high real interest rates. It is emphasized that the level of economic and financial literacy of people and the responsibility of financial institutions-creditors, which should clearly and easily explain to potential borrowers all the characteristics of the loan product and related risks, provide repayment schedules. loan obligations under different options, to announce the real cost of the loan and the amount of interest and commissions payable. It is proved that the impact of the use of credit services on the financial security of households is ambiguous, as it depends on the conscious attitude of both individuals and financial institutions-creditors to determine the amount of the required loan, its terms and the creditworthiness of borrowers. There are significant risks for both sides of the credit relationship, which legal regulation has recently significantly improved the protection of the financial interests of individual borrowers, which will help to maintain a sufficient level of the financial security of their households.